Do cost-sharing and entry deregulation curb pharmaceutical Innovation? - Volker Grossmann (Center for Economic Studies and ifo Institute (CESifo), 2011)
This paper examines the role of both cost-sharing schemes in health insurance systems and entry regulation for pharmaceutical R&D expenditure, drug prices, aggregate productivity, and income. The analysis suggests that both an increase in the coinsurance rate and stricter price regulations adversely affect R&D spending in the pharmaceutical sector. In contrast, entry deregulation may lead to quality-improvements of pharmaceuticals, despite reducing price-setting power of pharmaceutical companies. Extension to an endogenous growth context suggests that, when individual labor supply depends on health status, both cost-sharing and entry barriers in the pharmaceutical sector also affect aggregate productivity and wage rates.
Keywords: I10; L10; O30; 330; aggregate productivity; cost-sharing; entry deregulation; health insurance; pharmaceutical innovation; Pharmazeutische Forschung; Forschungsfinanzierung; Kostenbeteiligung; Gesetzliche Krankenversicherung; Markteintritt; Gesundheitsökonomik; Produktivität; Neue Wachstumstheorie; Theorie